Case Study of the Environmental Noise and its Perception in the City of Cluj-Napoca, Romania - POPESCU, Diana Ioana (Archives of Acoustics, 2020)
The noise perceiving issue is very subjective and depends on several factors, such as: the living environment in which each person has grown and developed, the education they have received, the culture in which their life principles have formed and, last but not least, the social and financial status. Therefore, in order to establish effective actions in multiple directions when it comes to any urban noise analysis, it is very important to know the perception and the subjective reactions of the individuals involved. The paper respects this idea, presenting the results of a sociological study on urban noise, applied in the city of Cluj-Napoca, Romania. The intention was to capture the reactions of the permanent residents of the city, but also of the people in transit, as well as to analyse the changes that occurred as result of the implementation of the Environmental Noise Directive (European Commission). The study shows that 75.2% of the respondents consider that the noise in the city has increased in the last ten years and 58% of them have rated the noise as level 4 or 5 on a five point scale. Information related to noise maps and actions taken to reduce community noise has no sufficient dissemination. There is also a medium to low reaction of the population in correlation to the declared noise annoyance.